Design of a Front-End for Satellite Receiver - Tran Van Hoi; Ngo Thi Lanh; Nguyen Xuan Truong; Nguyen Huu Duc; Bach Gia Duong (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper focuses on the design and implementation of a front-end for a Vinasat satellite receiver with auto-searching mechanism and auto-tracking satellite. The front-end consists of a C-band low-noise block down-converter and a L-band receiver. The receiver is designed to meet the requirements about wide-band, high sensitivity, large dynamic range, low noise figure. To reduce noise figure and increase bandwidth, the C-band low-noise amplifier is designed using T-type of matching network with negative feedback and the L-band LNA is designed using cascoded techniques. The local oscillator uses a voltage controlled oscillator combine phase locked loop to reduce the phase noise and select channels. The front-end has successfully been designed and fabricated with parameters: Input frequency is C-band; sensitivity is greater than -130 dBm for C-band receiver and is greater than -110dBm for L-band receiver; output signals are AM/FM demodulation, I/Q demodulation, baseband signals.